(untitled) (Bangladesh Journal of Medical Science, 2018)
Aims: This study aimed to determine the effect of probiotic combination on ratio of IFN-γ: IL-4 levels in patients with allergic rhinitis. Materials and methods: Single blind, randomized controlled trial.This study included 40 patients with severe allergic rhinitis according to WHO criteria. This study used 2 treatment groups with probiotics and placebo control group. IFN γ and IL-4 levels were evaluated using ELISA method. Data were analyzed using paired T test with 95% confidence intervals Results and Discussion: In the treatment group, the levels of IFN-γ increased significantly (p<0.05).In contrast, IL-4 levels decreased significantly(p<0.05). There was a significant difference between the IFN-γ ratio: IL-4 treatment and control group (p <0.05). Conclusion: The administration of combination of probiotics can improve the levels of IFN-γ/ IL-4 in patients with moderate to severe allergic rhinitis. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.42-45